(untitled) - Worthing, Marcia (Hoboken, N.J., 2008)
Whether you’re bored, burned out, retired, or fired, Escape the Mid-Career Doldrums offers solutions, ideas, and practical tools for shaking up your professional life for the better. Based on real case studies, this smart and practical career guide will help you discover the causes of your professional problems and give you the inspiration and confidence to take action and seize new opportunities. This is the perfect prescription for a new and exciting professional life
Keywords: Career changes,Vocational guidance,Mid-career,Occupational mobility,Thay đổi nghề nghiệp,Hướng nghiệp